2016
DOI: 10.1161/circimaging.115.004376
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Myocardium at Risk for Left Anterior Descending Artery, Right Coronary Artery, and Left Circumflex Artery Occlusion Depicted by Contrast-Enhanced Steady State Free Precession and T2-Weighted Short Tau Inversion Recovery Magnetic Resonance Imaging

Abstract: A fter occlusion of a coronary artery, an area corresponding to the perfusion territory of that artery becomes ischemic and will become infarcted unless timely reperfusion occurs. [1][2][3][4][5][6] This area is known as the myocardium at risk (MaR), and it can be used to calculate myocardial salvage index, 7 which is currently used as an end point in at least 19 ongoing clinical trials (Appendix I in the Data Supplement).Background-Contrast-enhanced steady state free precession (CE-SSFP) and T2-weighted short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
1
16
1
1
Order By: Relevance
“…These changes include increased myocardial extracellular volume fraction (Jablonowski et al, ) and alterations in T1 and T2 properties which can be utilized for quantification of MaR using CE‐SSFP by MR (Nordlund et al, ; Sorensson et al, ). MaR by CE‐SSFP has been shown to be stable over the first week after the acute event (Nordlund, Klug, et al, ) and this technique enables detailed depiction of MaR for all the major coronary arteries (Nordlund, Heiberg, et al, ). Infarct size can be assessed by LGE MRI (Kim et al, ) and compared to the initial MaR for calculation of myocardial salvage.…”
Section: Discussionmentioning
confidence: 99%
“…These changes include increased myocardial extracellular volume fraction (Jablonowski et al, ) and alterations in T1 and T2 properties which can be utilized for quantification of MaR using CE‐SSFP by MR (Nordlund et al, ; Sorensson et al, ). MaR by CE‐SSFP has been shown to be stable over the first week after the acute event (Nordlund, Klug, et al, ) and this technique enables detailed depiction of MaR for all the major coronary arteries (Nordlund, Heiberg, et al, ). Infarct size can be assessed by LGE MRI (Kim et al, ) and compared to the initial MaR for calculation of myocardial salvage.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Nordlund et al, 17 out of 215 CMR scans acquired using technology from different vendors, only 11 CE-SSFP sets were not of diagnostic quality. The scans from 2 other patients were of diagnostic quality, but the area at risk was not apparent.…”
Section: Utility Of Ce-ssfp Imagingmentioning
confidence: 95%
“…The temporal resolution of CE-SSFP was 20 to 30 frames per second. Nordlund et al 17 also set out to compare their results with previous publications on identifying the culprit artery using single photon emission computed tomography. 18,19 The CMR image analyses were performed in a core laboratory using software designed by the same group in the University of Lund, Sweden.…”
Section: Relationship Between the Culprit Artery The Myocardial Areamentioning
confidence: 99%
See 1 more Smart Citation
“…None of the above RCTs have however evaluated the effects of supplemental O 2 therapy in patients with STEMI based on the culprit vessel. It has been shown that Left Anterior Descending (LAD) infarction results in both a larger myocardium at risk and a larger infarct size [17] in comparison to non-LAD infarctions. As supplemental O 2 therapy has been suggested to increase oxygen delivery [18][19][20][21][22], it could thereby theoretically have a role in LAD infarcts.…”
Section: Introductionmentioning
confidence: 99%